PECULIARITIES OF THE ORGANIZATION OF MULTI-ETHNIC, CONVENED MAHALLAS DURING THE YEARS OF INDEPENDENCE (American Journal of Research in Humanities and Social Sciences, 2023)
The article examines the topical problems of reforming the system of makhallas in Uzbekistan, the peculiarities of organizing the activities of multinational, religious communities and democratic factors in the years of independence, It is narrated on the content of the Mahallabay Working System.